2017
DOI: 10.1002/ca.22918
|View full text |Cite
|
Sign up to set email alerts
|

Detailed anatomy of the abducens nerve in the lateral rectus muscle

Abstract: The aims of this study were to elucidate the detailed anatomy of the abducens nerve in the lateral rectus muscle (LRM) and the intramuscular innervation pattern using Sihler staining. In this cohort study, 32 eyes of 16 cadavers were assessed. Dissection was performed from the LRM origin to its insertion. The following distances were measured: from LRM insertion to the bifurcation point of the abducens nerve, from LRM insertion to the entry site of the superior branch or inferior branch, from the upper border … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 21 publications
2
13
0
4
Order By: Relevance
“…In our study, the same distance had a mean of 37.38 mm (SD = 6.21 mm). Nam et al () also noted that the superior group of the abducens nerve subbranches entered the lateral rectus muscle more anteriorly than did the inferior group, and we observed the same relations in our study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, the same distance had a mean of 37.38 mm (SD = 6.21 mm). Nam et al () also noted that the superior group of the abducens nerve subbranches entered the lateral rectus muscle more anteriorly than did the inferior group, and we observed the same relations in our study.…”
Section: Discussionsupporting
confidence: 90%
“…In their study, the muscle's mean length was 46.0 mm long, while it was 48.73 mm (SD = 1.03 mm) in ours. Nam et al (), who investigated the abducens nerve's detailed anatomy in the lateral rectus muscle, found that the single trunk of the abducens nerve divided into two branches 37 mm from insertion in the lateral rectus muscle. In our study, the same distance had a mean of 37.38 mm (SD = 6.21 mm).…”
Section: Discussionmentioning
confidence: 99%
“…Lateral movement of the eyeball is the primary function of the LR [1,2,8]. However, the recent studies indicate the complex activity of the LR, with the existence of the functional compartments (zones) within the muscle, which may be activated selectively depending on the type and phase of movement [2][3][4][17][18][19][20][21][22].…”
Section: Lateral Rectus Musclementioning
confidence: 99%
“…e statement of Farzavandi [1], who concluded that "An intimate knowledge of anatomy, including the extraocular muscles, periocular fascia, and orbit, is necessary to be an accomplished strabismus surgeon," became a motto of the presented review. Development of modern surgical techniques is associated with the need for a thorough knowledge of surgical anatomy and, in the case of ophthalmologic surgery, also functional aspects of extraocular muscles [1][2][3][4][5][6]. However, getting familiar with the numerous data that appear in various scientific journals may be difficult and time consuming.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation